Bacterial Contamination of Iranian Paper Currency. - Mir-Hassan Moosavy; Nassim Shavisi; Keith Warriner; Ehsan Mostafavi (Tehran University of Medical Sciences, 2013)
Transmission of human pathogens can be occurred via inert objects. Paper currency is a further common contact surface whereby pathogens can be transferred within a population although the significance remains unknown. Hence, the aim of the present study was to investigate microbial populations associated with Iranian paper currency.This study was carried out by getting 108 samples of the Iranian currency notes (1000, 2000, 5000, 10000, 20000 and 50000 RIALS) from food-related shops that included food service outlets, greengrocery, supermarket, bakery, confectionary and poultry meat retail outlets. All currency notes were examined for total bacterial count and identification of pathogenic bacteria.The average total bacterial count that was recovered from currency notes was found to be 3.27±0.31 colony forming unites.2000R had the highest total bacterial count, followed by 5000R, 10000R and the lowest in 50000R. In this study, the isolated bacteria recovered were Bacillus cereus (8.33%), E. coli (48.14%), Staphylococcus aureus(28.7%), Salmonella (0.92%), Listeria monocytogenes (0.92%), Yersinia entrocolitica(6.48%). It was revealed that all the pathogens screened for where encountered on currency notes were recovered from one sample. There were no significant (P>0.05) correlations between the carriage of pathogens/fecal indicator bacteria and currency note condition.Our findings demonstrate that Iranian currency notes represent a significant vehicle for human pathogens.